Chemical Youth Navigating Uncertainty in Search of the Good Life - Hardon, Anita (Critical Studies in Risk and Uncertainty,, 2021)
This open access book explores how young people engage with chemical substances in their everyday lives. It builds upon and supplements a large body of literature on young people's use of drugs and alcohol to highlight the subjectivities and socialities that chemical use enables across diverse socio-cultural settings, illustrating how young people seek to avoid harm, while harnessing the beneficial effects of chemical use. The book is based on multi-sited anthropological research in Southeast Asia, Europe and the US, and presents insights from collaborative and contrasting analysis. Hardon brings new perspectives to debates across drug policy studies, pharmaceutical cultures and regulation, science and technology studies, and youth and precarity in post-industrial societies.